The impact of grouping strategies on interaction effects and cognitive engagements in asynchronous online discussion - Pitagan, Ferdinand B. (Animo Repository, 2008)
In online learning, grouping provides a venue for engagements that could facilitate knowledge construction. Understanding how grouping strategies affect interaction and cognitive engagements during online discussion will provide better understanding and new knowledge critical to the success of online learning. Thus, the research employs a quasi-experiment using intact groups to investigate the type of interaction and level of cognitive engagements in homogeneous and heterogeneous groupings in asynchronous online discussion. The research employs pretesting as a grouping strategy and content analysis tools to examine the effects and implications.